Penerapan E-Catalog Terintegrasi Chatbot Decision Tree untuk Optimalisasi Layanan Penjualan - Puspitaningrum, Hapsari Retno; Subhiyakto, Egia Rosi (Universitas Hamzanwadi, 2025)
Digitalization drives business service optimization through more efficient and interactive systems. E-catalogs enable structured product information delivery but still have limitations in product search and customer interaction, which rely heavily on administrators. This study proposes the integration of a decision tree-based chatbot in a web-based e-catalog to enhance service efficiency and user experience. The prototyping method was implemented through four stages: requirement identification via interviews and observations, system design involving user interface and chatbot interaction flow, web-based implementation, and testing using Black-box Testing for functionality evaluation and the System Usability Scale (SUS) to measure user satisfaction. The results indicate that the system improves product search and ordering efficiency, with the chatbot providing automatic recommendations and reducing the workload of administrators. All system features functioned properly, and the SUS evaluation yielded an average score of 87.2. It is reflecting a high level of user satisfaction. The integration of chatbots in e-catalogs has proven to enhance service efficiency and customer interaction and can be applied to other SMEs facing challenges in digital promotion and order management.